Three new species of the Eriopisa group (Crustacea: Amphipoda: Eriopisidae) from Japan, with the description of a new genus - Ariyama, Hiroyuki (Zootaxa, 2015)
Three new species of the Eriopisa group (Crustacea: Amphipoda: Eriopisidae) are described from coastal areas in Japan. Paraflagitopisa gen. nov. is established with P. excavata sp. nov. as its type species. This new genus is characterized by (1) entire lateral cephalic lobe, (2) unfused flagellum of antenna 2, (3) 3-articulated mandibular palp, (4) carpus of gnathopod 1 longer than propodus, (5) transverse palm of gnathopod 1, and (6) slender outer ramus of uropod 3 with long second article, and can be distinguished from the closely related genus, Flagitopisa, by the article 2 of mandibular palp longer than article 3, the undilated bases of pereopods 3–4, and the slender inner ramus of uropod 3. Psammogammarus lobatus sp. nov. is characterized by (1) male gnathopod 2 with excavated palm, (2) posterodistally projected bases of pereopods 5–7, (3) quadrate posteroventral corner of pleonal epimeron 3, (4) short inner ramus of uropod 3, and (5) article 2 of uropod 3 outer ramus longer than article 1. Victoriopisa wadai sp. nov. has the following characters: (1) eyes absent, (2) peduncle of antenna 1 not heavily setose, (3) accessory flagellum with 1–2 articles, (4) flagellum of antenna 2 composed of 2 long and 3 short articles, (5) gnathopod 2 in both sexes with excavated palm, (6) merus of pereopod 7 moderately expanded, and (7) ventral margin of pleonite 2 slightly setose. Key to species of the Eriopisa group in Japan is provided.